TALENT MANAGEMENT IN ORGANIZATIONS: SYSTEMATIC LITERATURE REVIEW - Emi Amelia; Rofi Rofaida (Airlangga Journal of Innovation Management, 2023)
This study aims to look more comprehensively and in-depth from articles that have emerged about talent management in the span of time for the last 5 years (2017-2022). This research method uses Systematics of Literature Review by following the stages of PRISMA. The articles selected in this study were 40 articles from the initial search of 969 articles. Various aspects of talent management are explored in this literature review, including the process of talent discovery and selection, talent development and retention, and measuring the impact also success of talent management. Key findings from this study include differences in talent management approaches between organizations, the role of technology in facilitating talent management practices, and the importance of data measurement and analysis in understanding the impact of talent management programs. The study also found other research gaps, such as the impact of cultural context on talent management implementation and the impact of new technologies such as artificial intelligence. This systematic assessment of the literature offers a comprehensive understanding of the practices, difficulties, and possibilities associated with talent management. The findings from this research can be a significant resource for academics, practitioners, and corporate decision makers interested in developing and implementing a successful talent management system.